USE OF BLOCKCHAIN TECHNOLOGY IN DATA DISTRIBUTION SYSTEM SECURITY - Nur Hakim; Asri Ady Bakri; Farid Wahyudi (INJOSEDU: International Journal of Social and Education, 2025)
In the current digital era, data security is a major concern in various industrial sectors. Blockchain, as the data distribution technology underlying cryptocurrencies such as Bitcoin, has shown significant potential in addressing various data security issues. This literature research aims to comprehensively examine the use of blockchain technology in improving the security of data distribution systems. Through a systematic review method, this research collects and analyzes various studies, articles and reports related to the use of blockchain in the context of data security. The literature review results show that blockchain offers several key security features, such as decentralization, resistance to manipulation, anonymity, and transparency, which can prevent cyberattacks and protect data integrity. However, this research also identifies challenges faced in blockchain implementation, including issues of scalability, energy efficiency, and compatibility with existing data systems. This research suggests that the development of hybrid solutions that combine blockchain elements with traditional data distribution technologies can provide a balance between security and efficiency. Additionally, cooperation between developers, industry, and regulators is critical to creating standards and frameworks that support widespread blockchain adoption. Thus, this research provides a balanced view of the potential and challenges of using blockchain in the security of data distribution systems, as well as suggesting directions for further research and development in this area.